THE ADOPTION OF SAK EMKM IN THE PREPARATION OF FINANCIAL STATEMENTS OF MSMES: EVIDENCE FROM THE KIOS TAPE 13 COMMUNITY, INDONESIA - Wenny Djuarni; Denny Aditya Dwiwarman; Ira Mariah Ulfah; Mohammad Sigit Adi Nugraha (Prosiding Amal Insani Foundation, 2026)
This study aims to examine the adoption of Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) in the preparation of financial statements among MSMEs in the Kios Tape 13 community. MSMEs play a crucial role in Indonesia’s economy; however, many still face challenges in producing standardized and reliable financial reports. This research employs a qualitative descriptive approach using a case study method. Data were collected through interviews, direct observation, and documentation of financial records from selected MSME actors within the community. The findings reveal that the majority of MSMEs have not fully implemented SAK EMKM in their financial reporting practices. The main challenges identified include limited accounting knowledge, lack of awareness of accounting standards, absence of systematic bookkeeping practices, and constraints in human resources. Financial records are generally limited to simple cash inflow and outflow notes without proper classification of assets, liabilities, and equity. Nevertheless, MSME actors demonstrate a positive perception toward the potential benefits of SAK EMKM, particularly in improving financial transparency, supporting business decision-making, and facilitating access to external financing. This study proposes several strategic efforts to enhance SAK EMKM adoption, including targeted accounting training, simplified accounting guidelines, continuous mentoring, and collaboration with academic institutions and local stakeholders. The results are expected to contribute to the development of practical strategies for improving the quality of MSMEs’ financial reporting and to enrich the empirical literature on accounting standard adoption in developing economies.